The Effectiveness of Self-Surrender Exercise and Dzikir Therapy in Improving the Quality of Sleep in A Nursing Home in Pasuruan, Indonesia Road - Hidayat, Syaifurrahman (International Journal of Psychosocial Rehabilitation, 2020)
Old age is a phase of life that is often associated with decline. Physiological changes and psychological setbacks in old age can lead to a decrease in the quality of sleep or sleep disturbance. The practice of surrender is a method that combines relaxation and repetitive prayer. It eliminates anxiety and worry and provides a feeling of peace when done well. Dhikr relaxation is a form of passivity or resignation by using words that are repeated and which result in composure and relaxation. The purpose of this study was to investigate the effectiveness of self-surrender training and dhikr therapy in improving the quality of sleep for older people in the PSTW nursing home in Pasuruan, Indonesia. The study used a quasi-experimental design and purposive sampling. The population in this study were all older people in the PSTW nursing home in Pasuruan. The data were analyzed with the Mann-Whitney statistical test to distinguish between the two groups in the study. A Wilcoxon signed ranks test was used to determine the difference between the two paired samples. The results showed that before treatment, the majority of people (52%) reported poor sleep quality, but after treatment with self-surrender and dzikir therapy, 88.0% of people reported a good quality of sleep. The Wilcoxon signed ranks test, and the Mann-Whitney Test confirmed that the results were statistically significant. Self-surrender training and dhikr therapy can affect physical and psychological calmness. This calmness comes from within, in the form of words, short sentences, or thoughts that gave peace of mind and improved the quality of sleep for older people in the PSTW nursing home in Pasuruan.